Investigation of Waste Cooking Oil as a Tribological Lubricant for Piston Skirt Application - Amirruddin, Abdul Kadir; K., Kadirgama; D., Ramasamy; M. M., Noor; M. M., Rahman (2016)
This paper focuses on the analysis the influence lubricant properties. Lubricant is the liquid that mostly use in industry and in daily life especially for work needed. Lubricant usually use in the operation system especially in engine or machine to run efficiently in order to move on the process that needed. This research try to conduct in order to form the new formula for lubricant oil to be develop that involve the waste cooking and SAE40. For this research, the combination used for the lubricant are palm oil and the engine oil SAE40. In this research will use two sample that contain different ingredient. This project is take the waste cooking oil from the fast food company which is KFC and Mdonald. First sample for the waste cooking oil is using KFC waste cooking oil with load 2 kg at speed 200 RPM. The second sample is use the McDonald waste cooking oil with 2 kg load at 200 RPM. The last sample is use SAE40 with load 2kg for speed 200 RPM. The sample is repeating with othe different parameter of load and speed. The speed use in this project is 200 RPM and 300 RPM. Both sample will test by using wear and friction test with Aluminium 6061 as a specimen. The load applied is 20 N and 90N for both sample. The result will be obtain based on the surface structure of the Aluminium 6061 after use the microscopic lens in order to see its structure. From here, the research can determine the differences that appear based on the sample that already tested.